A new species of Sympodium (Octocorallia, Xeniidae) from Miyazaki, Japan - Koido, Tatsuki; Imahara, Yukimitsu; Fukami, Hironobu (Zootaxa, 2024)
In this study, a new soft coral species, Sympodium omasum sp. nov. (Malacalcyonacea, Xeniidae), is described from a warm-temperate region in Miyazaki, Japan. This new species has double-heads and platelet sclerites, and the platelets are covered with sinuous rodlets, which are fused and form many nodules at the sclerites surface. Sympodium omasum sp. nov. can be distinguished morphologically from a congeneric species by the double-head sclerites and unique platelet surface architecture.